Academics writing : the dynamics of knowledge creation - Tusting, Karin, 1973-; McCulloch, Sharon; Bhatt, Ibrar; Hamilton, Mary, 1949-; Barton, David, 1949- (Routledge, 2019)
"Academics Writing recounts how academic writing is changing in the contemporary university, transforming what it means to be an academic and how, as a society, we produce academic knowledge. Writing practices are changing as the academic profession itself is reconfigured through new forms of governance and accountability, increasing use of digital resources, and the internationalization of higher education. Through detailed studies of writing in the daily life of academics in different disciplines and in different institutions, this book explores: - the space and time of academic writing; - tensions between disciplines and institutions around genres of writing; - the diversity of stances adopted towards the tools and technologies of writing, and towards engagement with social media; and - the importance of relationships and collaboration with others, in writing and in ongoing learning in a context of constant change. Drawing out implications of the work for academics, university management, professional training and policy, Academics Writing: The Dynamics of Knowledge Creation is key reading for anyone studying or researching writing, academic support and development within education and applied linguistics"- Resumé vydavatel